Growth and Productivity Response of Hybrid Rice to Application of Animal Manures, Plant Residues and Phosphorus - Amanullah,; Khan, Shams-ul-Tamraiz; Iqbal, Asif; Fahad, Shah (Frontiers in Plant Science, 2016)
The objective of this research was to evaluate the impact of organic sources (animal manures vs. plant residues at the rate of 10 t ha-1 each) on the productivity profitability of small land rice (Oryza sativa L.) grower under different levels of phosphorus (0, 30, 60 and 90 kg P ha-1) fertilization. Two separate field experiments were conducted. In experiment (1), impact of three animal manures sources (cattle, sheep & poultry manures) and P levels was studied along with one control plot (no animal manure and P applied) as check was investigated. In experiment (2), three plant residues sources (peach leaves, garlic residues & wheat straw) and P levels was studied along with one control plot (no plant residues and P applied) as check. Both the experiments were carried out on small land farmer field at District Swabi, Khyber Pakhtunkhwa Province (Northwest Pakistan) during summer 2015. The results revealed that in both experiments the control plot had significantly (p≤0.05) less productivity than the average of all treated plots with organic sources and P level. The increase in P levels in both experiments (animal manure vs. plant residues) had resulted in higher rice productivity (90 = 60 > 30 > 0 kg P ha-1). In the experiment under animal manures, application of poultry manure increased rice productivity as compared with sheep and cattle manures (poultry > sheep > cattle manures). In the experiment under plant residues, application of peach leaves or garlic resides had higher rice productivity over wheat straw (peach leaves = garlic residues > wheat straw). On the average, the rice grown under animal manures produced about 20% higher grain yield than the rice grown under crop residues. We concluded from this study that application of 90 kg P ha-1 along with combined application of animal manures especially poultry manure could increase rice productivity. We conclude from this study that application of 90 kg P ha-1 along with combined application of animal manures, especially poultry manure, increases rice productivity. Also, the use of either garlic residues or peach leaves, never applied before as organic manures, can increase crop productivity